Upaya Meningkatkan Kemampuan Pemahaman Matematik Siswa Melalui Model Pembelajaran Kooperatif STAD Berbantuan Geoboard Materi Segi Empat dan Segitiga - Damanik, Novita Marlina (CARTESIUS : Jurnal Pendidikan Matematika, 2019)
This study aims to determine the improvement of students’ mathematical understanding abilities in class VII-2 SMP St. Thomas 3 Medan by applying the cooperative learning model type STAD assisted by geoboard. The method used in this research is classroom action research (CAR). The subjects in this study were students of class VII-2 St. Thomas Private School 3 Medan in the 2018/2019 Academic Year consisting of 32 students, 18 men and 14 women. From the research results it can be seen that there is an increase in students in students’ understanding ability by applying the geoboard-assisted type STAD cooperative learning model as follows: In the students’ mathematical early comprehension ability test is still realatively low, namely classical completeness obtained by 18.75% with very low categories. The results of the first cicle students’ mathematical understanding test that is obtained classical completeness of 53.12% with the medium category The results of the second cycle mathematical understanding test students obtained classical completeness 0f 84.37% with a high category. It can be seen that there is an increase starting from the ability of initial understanding, the ability to understand mathematical cycle I and mathematical understanding ability ability cycle II. So it can be concluded that the increase in students mathematical understanding abilities through the Geoboard-assisted STAD cooperative learning model increased from cycle I to cycle II, amounting to 31.25%.